Cover Image. Issue 12 (28th November 2017) - Siddiqui, Z. I.; Farooqui, S. R.; Azam, S. A.; Afroz, M.; Wajid, S.; Parveen, S.; Kazim, S. N.
Abstract : The cover image, by Z. I. Siddiqui et al., is based on the Original Article A comparative study of hepatitis B virus X protein mutants K130M, V131I and KV130/131MI to investigate their roles in fibrosis, cirrhosis and hepatocellular carcinoma, DOI:10.1111/jvh.12747 .